Measuring perception on the on-line service tax licensing system / Nor Haziah Abd Wahab and Jasmine Ahmad - Abd Wahab, Nor Haziah; Ahmad, Jasmine (2010)
This study measures client’s satisfaction on the usage of the on-line service tax license application and the processing officer’s perception on the performance of the on-line system. Service tax was initially charged and levied on prescribed goods sold or provided either by or in any prescribed establishment and on prescribed services provided by or in prescribed professional establishment. Over the years, there was an increase in the list of prescribed services and establishment. In 1999, the Service Tax Act 1975 was amended and as provided under section 3 of the Act, service tax is charged and levied on the provision of taxable service by any taxable person. A taxable person is defined as any person who is prescribed under the Act to be a taxable person and taxable services means any service which is prescribed to be a taxable service. The on-line service tax license application has been introduced to facilitate application of service tax license, in which it is available 24 hours a day and 7 days a week and can be accessed anywhere as long as there is internet access. However, the awareness level and the efficiency of the system have yet to be measured by the Royal Malaysian Customs Department (RMCD). The finding of this study would enable RMCD to decide on the need for promotional activities or enhancement of the on-line system.